Normality, abnormality, and pathology in Merleau-Ponty - Bredlau, Susan; Welsh, Talia (Albany : State University of New York Press, 2022)
"Drawing on Merleau-Ponty offers new insights into our understandings of health and illness, ability and disability, and the scientific and cultural practices that both enable and limit our capacity for diverse experiences"--
Front Matter -- Contents -- Acknowledgments -- Normality, Abnormality, and Pathology in Merleau-Ponty's Work -- Grounding a Phenomenology of Normality, Abnormality, and Pathology -- Toward a Phenomenology of Abnormality -- What Can We Learn about the Normal from the Pathological? -- Merleau-Ponty and Ab/Normal Phenomenology -- The Abnormalcy of "Normalcy" -- The Need for Merleau-Ponty in Foucault's Account of the Abnormal -- Practical Phenomenological Applications of Merleau-Ponty's Theories of Normality, Abnormality, and Pathology -- Meandering Peripheries -- The Insight of Dispossession -- Moving without Movement -- A Whole New World -- Health and Other Reveries -- The Desexualization of Disabled People as Existential Harm and the Importance of Ambiguity -- Works Cited -- Notes on Contributors -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 08, 2022).
JSTOR
Keywords: Public health -- Philosophy; Epidemiology -- Philosophy; Public health; Public Health; Santé publique -- Philosophie; Épidémiologie -- Philosophie; Santé publique; public health; PHILOSOPHY / Movements / Phenomenology; Epidemiology -- Philosophy; Public health -- Philosophy